Nanospheres as a technological alternative to suppress hepatic cellular damage and impaired bioenergetics caused by nerolidol in Nile tilapia (Oreochromis niloticus) - Baldissera M.D. (2020)
© 2020, Springer-Verlag GmbH Germany, part of Springer Nature.Nerolidol is a sesquiterpene found in essential oils of several plant species. It is found commonly in human and animal diets and is approved by the US Food and Drug Administration as a flavoring agent. Nevertheless, recent studies have suggested that nerolidol has potent hepatotoxic effects. Because use of plant-based products in human and animal food has expanded considerably, it is essential to develop approaches such as nanotechnology to avoid or reduce hepatic toxic effects. Therefore, the aim of the study was to determine whether nerolidol dietary supplementation elicited hepatic damage associated with impairment of energy homeostasis, as well as whether supplementation with nerolidol-loaded in nanospheres prevented hepatotoxic effects in Nile tilapia (Oreochromis niloticus). Nile tilapia were divided into five groups (A–E, n = 10 per group) with four replicates each, as follows: group A received basal feed (without supplementation); group B received feed containing 0.5 mL free nerolidol/kg; group C received feed containing 1.0 mL free nerolidol/kg; group D received feed containing 0.5 mL nanospheres nerolidol/kg; and group E received feed containing 1.0 mL nanospheres nerolidol/kg. All groups received experimental feed once a day (10% total biomass) at 2 p.m. for 60 consecutive days. Hepatic liver weight and relative liver weight were significantly lower in fish fed 1.0 mL free nerolidol/kg feed than in fish given basal diet (control group). Hepatic pyruvate kinase (1.0 mL free nerolidol/kg) and adenylate kinase (0.5 and 1.0 mL free nerolidol/kg) activities were significantly lower than in the control group, while hepatic reactive oxygen species and lipid damage levels were significantly higher. Finally, the comet assay revealed significant increases in the frequency of damage and the damage index in fish given 0.5 and 1.0 mL free nerolidol/kg in a dose-dependent manner. Nerolidol-loaded in nanospheres prevented all alterations elicited by free nerolidol. Based on these data, we concluded that dietary supplementation with free nerolidol elicited severe impairment of hepatic bioenergetics homeostasis that appeared to be mediated by excessive ROS production and lipid damage, contributing to a genotoxic effect. Dietary supplementation with nerolidol-loaded in nanospheres did not elicit hepatic damage, and therefore, should be considered as a replacement so as to limit toxicity, permitting its continued use as a dietary supplement.